Cross-sectional study of the prevalence of Babesia bigemina in Uganda : wildlife-livestock interface at and around LMNP - Schischke, Anna (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2015)
Ticks and the diseases they transmit are of major importance throughout the world. In Uganda, cattle are the most important livestock from an economic point of view. Livestock keepers fear bi-directional transmission of tick-borne pathogens between their livestock and wild animals. This cross-sectional study was conducted to establish and compare the sero-prevalence of the tick-borne pathogen Babesia bigemina among randomly selected Ankole Long-horned cattle and European crossbred cattle on 30 farms in Kiruhura district, in two sub-counties near Lake Mburo National Park in South-western Uganda. Half of the farms were situated in close proximity to the park and thereby housed cattle with more frequent wildlife-livestock interface (Sanga), whereas the other half had less frequent contact (Kikatsi). The sero-prevalence was established by detection of Babesia antibodies using a commercial Indirect Enzyme Linked Immunosorbent Assay (ELISA), Svanova Biotech AB, Uppsala Sweden. Blood smears from the same animals were also examined by microscopy. A structured questionnaire was applied to all participants with related questions to this study and ticks were collected for tick-burden estimation and tick species identification. A total of 130 animals were sampled, 63 in Sanga and 67 in Kikatsi, respectively. Only one animal was detected as positive by microscopy. The overall sero-prevalence was 26.9 ± 7.63 % and comparison showed a significant difference (P < 0.05) between the sub-counties of Sanga (44 ± 12.26 %) and Kikatsi (10 ± 7.18 %). This indicated that the wildlife-livestock interface may have a role in the epidemiology of B. bigemina, even if previous studies suggest the opposite. Confounders, such as management system, breed of the animal or tick burden did not show a significant difference when comparing the sero-prevalence of B. bigemina to the two sub-counties Sanga and Kikatsi. The different results from the present and a previous studies and also that confounders did not affect the sero-prevalence implies that more studies needed.